How do the practitioners perceive relevancy of lean practices in IT support services?. Issue 5 (10th August 2015) - Kundu, Goutam Kumar; Manohar, B. Murali; Bairi, Jayachandra
Abstract : Purpose: – The purpose of this paper is to capture and analyze the perception gaps with respect to the current usage and importances of the lean practices from the IT support service practitioners' perspective. Design/methodology/approach: – A questionnaire was developed to capture the perceptions of the IT support service practitioners. The survey data were quantitatively analyzed by using statistical techniques which included testing of the hypotheses. Findings: – The analysis of the perception gaps revealed that even though all the gaps are statistically significant but gaps between different practices are not same. The gap analysis would be useful for IT support service organization in prioritizing the lean practices for implementation. Originality/value: – Lean practice applicability and implementation in IT support services is a relatively new domain, where mature empirically based studies are scarce. This study provides a sound basis for further research on lean implementation in IT support service area.